2020
DOI: 10.1136/bmjdrc-2019-000767
|View full text |Cite
|
Sign up to set email alerts
|

Mining treatment patterns of glucose-lowering medications for type 2 diabetes in the Netherlands

Abstract: Rationale and objectivesDifferent classes of glucose-lowering medications are used for patients with type 2 diabetes mellitus (T2DM) management. It is unclear how often these medications are prescribed in clinical practice. In this study, we aimed to describe treatment patterns of glucose-lowering medications in patients with T2DM in the Netherlands.MethodsWe studied a cohort of 73 819 patients with T2DM, aged ≥45 years with a first prescription for oral glucose-lowering medication between 2011 and 2017. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…We determined the main treatment pathways based on the most frequent two-step combinations, which are changes from one treatment to another among at least 1% of pregnancies with antiemetic medication fills. 33 Treatment steps were considered the start (date of dispensing) and the end date (calculated from the number of DDDs dispensed) of prescription fills, taking into account the allowed gap of 14 days to correct for medication possession gaps due to non-adherence.…”
Section: Methodsmentioning
confidence: 99%
“…We determined the main treatment pathways based on the most frequent two-step combinations, which are changes from one treatment to another among at least 1% of pregnancies with antiemetic medication fills. 33 Treatment steps were considered the start (date of dispensing) and the end date (calculated from the number of DDDs dispensed) of prescription fills, taking into account the allowed gap of 14 days to correct for medication possession gaps due to non-adherence.…”
Section: Methodsmentioning
confidence: 99%
“…A 5‐year longitudinal study showed 84% of people with type 2 diabetes start biguanides (metformin). The next most common treatment (in 19% of cases) is biguanides + sulfonylurea 12 . Despite reimbursement of dapagliflozin when added to metformin plus sulfonylurea, use of dapagliflozin in the Netherlands is limited, partially due to cost considerations 13 .…”
Section: Introductionmentioning
confidence: 99%
“…NControl adheres to data protection and privacy regulations, as established in among others the Personal Data Protection Act in The Netherlands as well as The Netherlands Norm (NEN) 7510 standard on information protection in healthcare, which is derived from International Organisation for Standardization (ISO) norm 27001 and 27002. 15 …”
Section: Methodsmentioning
confidence: 99%
“…NControl adheres to data protection and privacy regulations, as established in among others the Personal Data Protection Act in The Netherlands as well as The Netherlands Norm (NEN) 7510 standard on information protection in healthcare, which is derived from International Organisation for Standardization (ISO) norm 27001 and 27002. 15 Subject and drug selection Selection of subjects was performed using the NControl database between 1 January 2013 and 1 January 2019. Chronic patients were defined based on the frequency by and the duration for which patients received dispensions of chronic disease-specific medications.…”
Section: Databasementioning
confidence: 99%